Perencanaan Struktur Cantilever Bentang Panjang Menggunakan Rangka Pratt Truss - Putu Axel Benyamin; Jonie Tanijaya; Benny Kusuma (Paulus Civil Engineering Journal, 2022)
In designing a truss cantilever structure with a predetermined long span, it will certainly look for a model of long-span structure with a profile that is able to withstand the given load. This can be done by planning a model of the pratt truss long-span structure. The main purpose of this final task is to produce a design of a long-span cantilever structure that is part of a unique building using a pratt truss model. The long-span pratt truss cantilever structure is analyzed using the MDSolids v.4.1.0 program to compute the inner forces working on each component of the designed frame structure, while the STAAD Pro Connect v.22 program analyzes the deformation of the design cantilever structure profile. The planning of this long-span cantilever structure is designed with reference to SNI 1727:2020 on minimum design load and related criteria for buildings and other structures, and SNI 1729:2020 on specifications for structural steel buildings. The result of the planning obtained is the dimensions of the beam bar profile needed. Pratt truss long-span structure is able for used as a cantilever long-span structure. This is seen from the results of calculations using computer programs where the pratt truss model has a deformation/deflection structure that occurs not exceeding the specified limit, and the results of the profile design used safely in receiving loads, although the results of calculation analysis there are the most critical rod elements in withstanding the load of the axial force of the press, namely the t1 and b2 rods. While the most critical rods in withstanding the load of axial force pull are the rods d1 and a1.English translation.